Investigação do uso do SERVQUAL em uma biblioteca: um estudo longitudinal - Figueiredo, Rute Aparecida (Universidade Federal de São Carlos, 2018)
The service quality provided by a university library is an important factor in user satisfaction, however because it is a multidimensional concept there are difficulties in relation to how it is evaluated. The aim of this study was to investigate the use of SERVQUAL in a university library using a longitudinal design. Thus, the research was divided into two stages. The first consisted of a systematic review of the literature on the assessment of service quality in a library to identify an overview of publications on service quality in libraries. The second stage consisted of investigating the impact of the interventions carried out between 2013 and 2017 in a university library on the dimensions of service quality, through the application of SERVQUAL in two moments combined with identification of interventions through a case study and an interpretative analysis impact of interventions. The results showed that the interventions had an impact on reducing the negative gaps in the service quality dimensions of the library under investigation. This study contributes to guide librarians in directing interventions related to improving the service quality provided to users.
Investigation of the use of SERVQUAL in a library: a longitudinal study
Keywords: Qualidade em serviços; Bibliotecas universitárias; Avaliação; Service quality; University libraries; Assessment; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO